Relationships between History of COVID-19 Disease, Anxiety, and Symptoms of Obsessive Compulsive Disorder (OCD) in Adolescents Age 20-24 Years - Christanti, Ayu Novia; Ningyas, Woro Setia; Karimah, Azimatul; Lestari, Pudji (Journal of Maternal and Child Health, 2023)
Background: The COVID-19 pandemic triggers anxiety and worry in society. Active cases have continued to grow since the government announced the first patient of COVID-19 in Indonesia. In the midst of the pandemic, adolescent is a dominant groups in society infected with COVID-19. This situation can affect the psychological condition of adolescents. This study aims to analyze the relationship between the history of COVID-19 and anxiety and symptoms of Obsessive Compulsive Disorder (OCD) in adolescents aged 20-24 years in Surabaya. Subjects and Method: A cross-sectional study was conducted in Surabaya City from October to November 2022. As many as 100 youth aged 20-24 years in Surabaya were the subjects of this study. The dependent variable is anxiety and obsessive compulsive disorder (OCD) symptoms. The independent variable is adolescents aged 20-24 years with a history of COVID-19. The instruments used were questionnaires and PCR swab evidence collection. Research data were analyzed using Pearson's correlation. Results: The results showed that 74 subjects (74%) had mild anxiety. Meanwhile, there were 16 subjects (16%) who had symptoms of OCD. Analysis of the chi-square correlation test between history of COVID-19 disease and anxiety showed that there was no relationship between the two variables with a p value = 0.704. Analysis of the chi-square correlation test between history of COVID-19 disease and OCD symptoms showed that there was no relationship between the two variables with a p value = 0.086. Conclusion: There is no relationship between history of COVID-19 disease and anxiety in adolescents aged 20-24 years in Surabaya and there is no relationship between history of COVID-19 disease and symptoms of OCD in adolescents aged 20-24 years in Surabaya.   Keywords: COVID-19, anxiety, Obsessive Compulsive Disorder (OCD) symptoms. Correspondence: Ayu Novia Christanti. Study Program of Midwifery, Faculty of Medicine, Universitas Airlangga, Indonesia. Jl. Mayjen Prof. Dr. Moestopo 47, Pacar Kembang, Tambaksari, Surabaya, East Java 60132. Email: ayu.novia.christanti-2019@fk.unair.ac.id. Mobile: +6283849353637.